2020
DOI: 10.20546/ijcmas.2020.903.053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cherry Tomato (Solanum Lycopersicum L. var. cerasiforme) Genotypes for Growth and Yield Parameters

Abstract: Tomato (Solanum lycopresicum L.) is one of the most important solanaceous vegetable crops grown widely all over the world and is native to South America (Rick, 1969). Botanically cherry tomato is called Solanum lycopersicum var. cerasiforme having chromosome number 2n=24. It is thought to be the ancestor of all cultivated tomatoes. It is widely cultivated in Central America and is distributed in California, Korea, Germany, Mexico and Florida. It is a warm season crop reasonably tolerant to heat and drought and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The temperature inside the greenhouse was 21.32 ºC and 25.07 ºC, respectively. These ndings are in line with earlier research by Suyanto [40], which showed that tomato plants grow more quickly (1.11 cm/day) under 680 nm light than they do under lower wavelength light (480, 550, and 650 nm) at the germination stage. A study reported that the height of tomato plants appears signi cantly higher under 14-hour photoperiod treatment during the months of the spring season [41].…”
Section: Discussionsupporting
confidence: 92%
“…The temperature inside the greenhouse was 21.32 ºC and 25.07 ºC, respectively. These ndings are in line with earlier research by Suyanto [40], which showed that tomato plants grow more quickly (1.11 cm/day) under 680 nm light than they do under lower wavelength light (480, 550, and 650 nm) at the germination stage. A study reported that the height of tomato plants appears signi cantly higher under 14-hour photoperiod treatment during the months of the spring season [41].…”
Section: Discussionsupporting
confidence: 92%
“…Environmental variations, especially insufficient light, can significantly extend this timeframe by impeding starch and sugar export, leading to inadequate carbohydrate accumulation in bud source organs. This delay, in turn, hampers floral initiation and reduces the flower bud count [30].…”
Section: Discussionmentioning
confidence: 99%
“…Taller plants tend to exhibit a greater total number of flower clusters [29]. According to one study, the count of leaves produced before the appearance of the first inflorescence in tomato plants decreases with higher levels of light intensity [30]. At high temperatures, the relative growth rate (RGR) of tomato plants initially increases but rapidly drops over time, while at lower temperatures the growth rate is initially low but declines more gradually [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the winter season, short-term light exposure has an impact on a plant's metabolic processes and growth. A study correlated plant height with high productivity and better biomass calculations [40]. According to a research report, the temperature inside a greenhouse without an environment controller exceeds 20-30 °C as compared to the outside temperature [41].…”
Section: Discussionmentioning
confidence: 99%